Analisis Tata Kelola Aset Desa Berdasarkan Permendagri No 1 Tahun 2016 di Desa Baureno Kecamatan Baureno Kabupaten Bojonegoro - Hilmi Wahyu Irawan; I. B. Ketut Bayagkara (Manajemen Kreatif Jurnal, 2023)
Baureno Village, which is located on Jalan Raya Baureno, is the Village Government Office which operates in the government sector, Baureno Village itself is a village located in east end of Bojonegoro Regency. The purpose of this research is to analyze the process of planning, procurement, administration, reporting and supervision of village assets in Baureno Village, Bojonegoro Regency, the inhibiting factors and efforts made to resolve them problem. This is a qualitative research with a case study approach. Data obtained through interview techniques, observation and documentation. The research results show that the processes of planning, procurement, administration, reporting and supervision are appropriate and not in accordance with the Regulation of the Minister of Home Affairs Number 1 of 2016 concerning Village Asset Management. Besides that, the mandate of the Village Law is to make an inventory of everything Village assets have not been fully implemented by the village government. The obstacles faced are village asset management funding, funds that are not on target, frequent siskeudesa applications errors, implementation that is not in accordance with the rules, lack of activity executors in responding market prices, human resources and transparency. Suggestions that can be given are for more focus on addressing the funds to be budgeted for the management of village assets, conducting inventory of assets in accordance with the provisions of the law.